Clinical effects of lateral wedge arch support insoles in knee osteoarthritis: A prospective double-blind randomized study. Issue 27 (July 2016) - Hsieh, Ru-Lan; Lee, Wen-Chung
Abstract : Abstract: We compared the short-term efficacy of rigid versus soft lateral wedge arch support (LWAS) insoles for patients with knee osteoarthritis (OA), as assessed using the International Classification of Functioning, Disability and Health (ICF) system, through a prospective, double-blind, randomized controlled trial. Participants who fulfilled the combined radiographic and clinical criteria for knee OA, as defined by the American College of Rheumatology, were randomly prescribed 1 pair of rigid or soft LWAS insoles. Body functions and structures were evaluated according to Kellgren–Lawrence scores, the Foot Posture Index, Hospital Anxiety and Depression Scale scores, the pain–pressure threshold, postural stability, dynamic balance, and fall risk; activities and participation were assessed according to 10-m fast speed walking, stair climbing and chair rising times, and Chronic Pain Grade questionnaire responses; and knee OA-related health status was evaluated using the Knee Injury and Osteoarthritis Outcome Score (KOOS). Hospital Anxiety and Depression Scale scores, the pain–pressure threshold, physical activity, balance, Chronic Pain Grade questionnaire responses, and the KOOS were recorded before treatment and at 1-, 2-, and 3-month follow-ups. We enrolled 90 participants, 70 women and 20 men, with mean ages of 60.6 ± 10.8 and 63.1 ± 10.8 years in the rigid and soft LWAS insole groups, respectively. Repeated-measures analysis of covariance revealed significant time × group effect improvements in pain ( P = 0.008 for the KOOS), stair ascent time ( P = 0.003), daily living function ( P = 0.003 for the KOOS), sports and recreation function ( P = 0.012 for the KOOS), and quality of life ( P = 0.021 for the KOOS) in the soft LWAS insole group. Patients with knee OA who used soft LWAS insoles for a short term showed more significant improvement than did those who used rigid LWAS insoles in pain, physical activity, daily living function, sports and recreation function, and quality of life, which belong to the body functions and structures and the activities and participation components in the ICF scheme.